ANALYTICAL REVIEW OF INFORMATION FOR TESTING THE OPEN PARAMETRIC SYSTEM OF AUTOMATED PROJECTION «VALENTINA» - ZASORNOVA, Iryna; ZASORNOV, Alexander; MAZNIEV, Ievgen; SARANA, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes proprietary systems, such as Lectra systems (France), Gerber Garment Technology (USA), Investronika (Spain), Assyst GmbH (Germany), Wild Ginger Software (USA) and open PatternViewer (USA), Valentina (Ukraine) automated design systems for sewing production. An analytical review of the information for testing the open parametric system of automated projection and design «Valentina» was performed. It was determined that the theoretical foundations of automated testing of automated design systems are currently an incompletely resolved problem. The minimum list of data for qualitative testing is presented, which contains 10 items, the main of which are: listings of source texts of software products, external specification, test plan and methods, test options and obtained results. The article provides a list of Internet sources of the «Valentina» software product distribution, a list of communication methods, as well as a list of external specification items required for testing the «Valentina» software product. Various versions of the «Valentina» were considered, as well as the changes made in the test version v0.7.52 compared to the previous version v0.7.51. Various types of errors that occur during the development of new functions of software products are analyzed, including the inability to perform one of the functions; inability to complete a function; the appearance on the screen of symbols or program primitives that do not correspond to the action; involuntary closing of the program window; closing the program window without warnings about saving data; other errors. The information obtained for testing the open parametric system of automated projection «Valentina» can be used in the future for the analysis of methods of testing software products and their improvement, as well as for the development of automated tests that can be implemented in the processes of creating and operating software products.